Isolation and functional characterization of the novel Clostridium botulinum neurotoxin A8 subtype. - Skadi Kull; K Melanie Schulz; Jasmin Weisemann; Sebastian Kirchner; Tanja Schreiber; Alexander Bollenbach; P Wojtek Dabrowski; Andreas Nitsche; Suzanne R Kalb; Martin B Dorner; John R Barr; Andreas Rummel; et al. (PLoS ONE, 2015)
Botulism is a severe neurological disease caused by the complex family of botulinum neurotoxins (BoNT). Based on the different serotypes known today, a classification of serotype variants termed subtypes has been proposed according to sequence diversity and immunological properties. However, the relevance of BoNT subtypes is currently not well understood. Here we describe the isolation of a novel Clostridium botulinum strain from a food-borne botulism outbreak near Chemnitz, Germany. Comparison of its botulinum neurotoxin gene sequence with published sequences identified it to be a novel subtype within the BoNT/A serotype designated BoNT/A8. The neurotoxin gene is located within an ha-orfX+ cluster and showed highest homology to BoNT/A1, A2, A5, and A6. Unexpectedly, we found an arginine insertion located in the HC domain of the heavy chain, which is unique compared to all other BoNT/A subtypes known so far. Functional characterization revealed that the binding characteristics to its main neuronal protein receptor SV2C seemed unaffected, whereas binding to membrane-incorporated gangliosides was reduced in comparison to BoNT/A1. Moreover, we found significantly lower enzymatic activity of the natural, full-length neurotoxin and the recombinant light chain of BoNT/A8 compared to BoNT/A1 in different endopeptidase assays. Both reduced ganglioside binding and enzymatic activity may contribute to the considerably lower biological activity of BoNT/A8 as measured in a mouse phrenic nerve hemidiaphragm assay. Despite its reduced activity the novel BoNT/A8 subtype caused severe botulism in a 63-year-old male. To our knowledge, this is the first description and a comprehensive characterization of a novel BoNT/A subtype which combines genetic information on the neurotoxin gene cluster with an in-depth functional analysis using different technical approaches. Our results show that subtyping of BoNT is highly relevant and that understanding of the detailed toxin function might pave the way for the development of novel therapeutics and tailor-made antitoxins.